PERJUANGAN TOKOH PEREMPUAN DALAM NOVEL TANAH TABU KARYA ANINDITA S. THAYF: KAJIAN FEMINISME EKSISTENSIALIS - Geleuk, Maria Benga; Mulawarman, Widyatmike Gede; Hanum, Irma Surayya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2017)
ABSTRACT The purposes of this research were to describe the factual structure and the struggle of female characters in “Tanah Tabu” novel by Anindita S. Thayf in terms of existentialist feminism. The researcher was interested to analyze “Tanah Tabu” novel, because this novel presented female characters that can fight to get freedom. The type of this research was descriptive qualitative method, which obtains the information and the description of the struggle of the female characters in “Tanah Tabu” novel based on existentialist feminism. This research used structural approach. The source of data in the research was from “Tanah Tabu” novel by Anindita S. Thayf. Data collection techniques in this research such as read, corect, and write. Meanwhile, data analysis techniques were provided in three phases such as data reduction, data presentation, and conclusion drawing. The result of this research shows the factual structure of the “Tanah Tabu” novel by Anindita S. Thayf, consisting of characters characterization, plot, and setting. This novel used flashback plot. The characters in this novel have a role as the main character and additional characters. The setting was in Papua, which shows the life of Papua society. The story time shows the year 2012, 1946, 1956, 1958, and 1960. The struggle of female characters in the “Tanah Tabu” novel by Anindita S. Thayf based on existentialist feminism, consists of awareness as liyan, freedom, and transcendence. Awareness as a liyan occurs in Mabel, Mace, and Mama Helda. These three female characters realized that they have been oppressed. Through the awareness, they choose to fight to get out of the oppression. The freedom is owned by Mabel, Mace, and Mama Helda. They are free to make choices which they hold as true and brave to responsible for their decision. Transcendence is performed by Mabel, Mace, and Mama Helda. They became working women, intellectual women, women of socialist transformation, and women follow dominant groups. Key words: female character, novel, existentialist feminism ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan fakta cerita dan perjuangan tokoh perempuan dalam novel Tanah Tabu karya Anindita S. Thayf ditinjau dari feminisme eksistensialis. Penulis tertarik mengkaji novel Tanah Tabu, karena novel ini menghadirkan tokoh perempuan yang mampu berjuang mendapatkan kebebasan. Jenis penelitian ini menggunakan metode kualitatif deskriptif, yaitu untuk memperoleh informasi dan gambaran perjuangan tokoh perempuan dalam novel Tanah Tabu berdasarkan feminisme eksistensialis. Penelitian ini menggunakan pendekatan struktural. Sumber data penelitian adalah novel Tanah Tabu karya Anindita S. Thayf. Teknik pengumpulan data menggunakan teknik baca, simak, dan catat. Teknik analisis data menggunakan reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukan bahwa fakta cerita novel Tanah Tabu karya Anindita S. Thayf, terdiri atas alur, tokoh penokohan, dan latar. Tokoh dalam novel ini mempunyai peranan sebagai tokoh utama dan tokoh tambahan. Latar berada di Papua dengan latar suasana kehidupan masyarakat Papua. Waktu cerita menunjukan tahun 2012, 1946, 1956, 1958, dan 1960. Novel ini menggunakan alur mundur. Perjuangan tokoh perempuan dalam novel TanahTabu karya Anindita S. Thayf berdasarkan feminisme eksistensialis, terdiri atas kesadaran sebagai liyan, kebebasan, dan transendensi. Kesadaran sebagai liyan terjadi pada Mabel, Mace, dan Mama Helda. Ketiga tokoh ini menyadari telah tertindas. Melalui kesadaran ini pula, mereka memilih berjuang untuk keluar dari ketertindasan. Kebebasan dimiliki oleh Mabel, Mace, dan Mama Helda. Mereka bebas menentukan pilihan yang mereka anggap benar dan berani bertanggung jawab atas pilihan tersebut. Transendensi dilakukan oleh Mabel, Mace, dan Mama Helda. Mereka menjadi perempuan pekerja, perempuan intelektual, perempuan transformasi sosialis, dan perempuan mengikuti kelompok dominan. Kata kunci: tokoh perempuan, novel, feminisme eksistensialis